6 - Education et identité des « Portugais » en Casamance XIXè-début XXè1 Histoire d’une « assimilation » manquée ? - Céline Labrune-Badiane, (Afrika Zamani, 2022)
The story of Luso-Africans began with the arrival of Portuguese explorers in the fifteenth century, more specifically in Casamance in the seventeeth century. The identity of these mulatos was built up through their successive relationships zith the Africans, the Portuguese and the French. The Luso-Africans created a unique society and strengthens their ties by setting up economic networks and by implementing social and educative strategies. Zinguinchor’s «Portuguese» sent their children to local schools that were established by missionaries or the Europe. They continued claiming their European origins despite the long running French assimilation project implemented since the nineteenth century. They gradually lost their power both in the political and economic fields despite their relative social success because of their dwindling population. They became marginalized as pre-colonial Senegal was centralized in Dakar